Effect of Simple Myopic Astigmatism and Its Axis on Near Visual Performance for Thai Alphabet in Pseudophakic Eyes - Pakviwat P; Moollaong C; Borvonshivabhumi S; Roongpoovapatr V (Clinical Ophthalmology)
Pakpum Pakviwat, Chureeporn Moollaong, Sasinut Borvonshivabhumi, Vatookarn Roongpoovapatr Department of Ophthalmology, Mettapracharak (Wat Rai Khing) Hospital, Nakhon Pathom, ThailandCorrespondence: Pakpum Pakviwat, Department of Ophthalmology, Mettapracharak (Wat Rai Khing) Hospital, 52 Moo 2 Rai Khing District Sampran, Nakhon Pathom, 73210, Thailand, Email eformx.pp@gmail.comBackground: Refractive target of low simple myopic astigmatism allows increased depth-of-focus and near visual performance in monofocal intraocular lens (IOL) implants. This study investigated the effect of astigmatism and its axis on distance and near visual acuity (VA), and near visual performance for the Thai alphabet using the Thai MNREAD chart.Design: Investigational simulation.Methods: Distance (6.0 m) VA, near (40 cm) VA and near visual performance (maximum reading speed [MRS], threshold print size [TPS] and reading acuity [RA]), were assessed by the Thai MNREAD chart monocularly in 31 pseudophakic eyes (62.8 ± 8.55 years). Six refractive conditions were simulated using trial lenses: ± 0.00 DS [in-focus at distance], +1.00 × 90 [ATR (Against-the-Rule)], +2.00 × 90 [ATR], +1.00 × 180 [WTR (With-the-Rule)], +2.00 × 180 [WTR], and +3.00 DS [in-focus at near].Results: Distance VA was degraded by spherical and astigmatic defocus compared with +0.00 DS [in-focus (distance)] (p < 0.001). No significant difference in distance VA was found between ATR and WTR astigmatism at the same magnitude. Near VA was better with +3.00 DS (p-value < 0.001) compared with other refractive conditions. Near visual performance (threshold print size [TPS]) was significantly better in ATR compared with WTR astigmatism (p < 0.001 for both +1.00 DC and 2.00 DC).Conclusion: Low simple myopic astigmatism improved near visual performance in monofocal IOL implants at the expense of degradation of distance VA. ATR astigmatism provided better TPS than WTR astigmatism. This benefit of ATR over WTR astigmatism on reading performance on the Thai alphabet confirmed the role of axis orientation on near visual performance.Keywords: low simple myopic astigmatism, monofocal intraocular lens(IOL), IOL, near visual performance, Thai MNREAD chart(Minnesota low vision reading chart), Minnesota low vision reading chart, against-the-rule astigmatism, ATR, distance visual acuity(VA), VA